Foreign banks and credit volatility: The case of Latin American countries - Meriem Haouat; Diego Nicolas Moccero; Ramiro Sosa Navarro (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
Foreign bank presence has substantially increased in Latin America during the second half of the 1990s, which has prompted an intense debate on its banking and macroeconomic consequences. In this paper, we apply ARCH techniques to jointly estimate the impact of foreign bank presence on the level and volatility of real credit in a panel of eight Latin American countries, using quarterly data over the period 1995:1-2001:4. Results show that, together with financial development, foreign bank presence has contributed to reduce real credit volatility, improving the buffer shock function of the banking sector. This finding is consistent with the fact that foreign banks are typically well diversified institutions holding higher quality assets and having access to a broad set of liquidity sources.
Keywords: C33; E51; G21; 330; foreign banks; credit volatility; Latin America; panel data; ARCH techniques